Citrix XenDesktop 7 cookbook : over 35 recipes to help you implement a fully featured XenDesktop 7 architecture with a rich and powerful VDI experience /: over 35 recipes to help you implement a fully featured XenDesktop 7 architecture with a rich and powerful VDI experience. (2014) - Unknown
No abstract available